2010
DOI: 10.1109/tnet.2009.2024941
|View full text |Cite
|
Sign up to set email alerts
|

Deploying Sensor Networks With Guaranteed Fault Tolerance

Abstract: We consider the problem of deploying or repairing a sensor network to guarantee a specified level of multipath connectivity (k-connectivity) between all nodes. Such a guarantee simultaneously provides fault tolerance against node failures and high overall network capacity (by the max-flow min-cut theorem). We design and analyze the first algorithms that place an almost-minimum number of additional sensors to augment an existing network into a k-connected network, for any desired parameter k. Our algorithms hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(70 citation statements)
references
References 58 publications
0
70
0
Order By: Relevance
“…Each sensor normally requires a lightweight computation (in many cases, 0/1 decision for the event detection). There are plenty of deployment approaches proposed by computer science researchers focusing on this research area [Chang et al 2011;Wang et al 2008;Kashyap et al 2011;Krause et al 2011;Xue et al 2012;Xu et al 2010;Bredin et al 2010].…”
Section: Difficulties In Applying Generic Wsn Placement Approaches Fomentioning
confidence: 99%
“…Each sensor normally requires a lightweight computation (in many cases, 0/1 decision for the event detection). There are plenty of deployment approaches proposed by computer science researchers focusing on this research area [Chang et al 2011;Wang et al 2008;Kashyap et al 2011;Krause et al 2011;Xue et al 2012;Xu et al 2010;Bredin et al 2010].…”
Section: Difficulties In Applying Generic Wsn Placement Approaches Fomentioning
confidence: 99%
“…The work given in [9] addresses the problem of deploying relay nodes to provide fault tolerance with higher network connectivity in heterogeneous wireless sensor networks, where sensor nodes possess different transmission radii. The wo rk given in [10] considers the problem of deploying or repairing a sensor network to guarantee a specified level of mu ltipath connectivity (k-connectivity) between all nodes. The work given in [11] presents a method for monitoring, maintaining and repairing the communication network of a dynamic mobile wireless sensor network, so that network connectivity is continuously available and provides fault tolerance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Experimental results showed that this solution had a 3D obstacles avoidance with better network fault tolerance and the optimized placement position feature. Reference [24][25][26][27][28][29][30][31] aimed to establish fault tolerant sensor network, and they proposed profound theories and algorithms based on Steiner and other graphic theories. But these researches did not consider the industrial environment in practice; for example, the influence of sink node position, network delay, and overall energy consumption was not considered.…”
Section: Related Work On Relay Node Placementmentioning
confidence: 99%